Study of education and memory of descendants in the quality of additional loading of aqueous plant extracts - О. N. Pavlova; O. N. Gulenko; V. V. Maslyakov; E. S. Kanaeva; M. L. Temkin; A. Yu. Kirillov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
As the body ages, free radical processes intensify and the risk of various age-related diseases increases, including memory impairment, as exchange processes in nerve cells deteriorate. The internal antioxidant system, capable of neutralizing free radicals, is not always able to cope with the growing load, and then the supply of antioxidants from outside is necessary. A source of biologically active substances possessing antioxidant activity are plant extracts possessing a pronounced therapeutic effect combined with a minimum of side effects. The purpose of our study was to study the learning and memory of the offspring of rats that received aqueous plant extracts as an additional load. The study of the learning and memory of the offspring of rats that received aqueous plant extracts of Ginkgo biloba, Centella asiatica, Eleutherococcus and a mixture of aqueous extracts of Ginkgo biloba and Centella asiatica was performed on 4-month-old animals, obtained in an experiment from 15 males and 50 females, which in the course of 30 days water extracts were obtained in a dose of 30 mg/100 g of body weight in a volume of 1 ml. The study was carried out with the help of the test "Passive escape with negative (painful) reinforcement". Conclusions: the offspring of rats that received as an additional load intragastric mixture of aqueous extracts of Ginkgo biloba and Centella asiatica are characterized by the best indicators of learning and memory, compared to the offspring of animals of the control group, and rats that received aqueous extracts of Ginkgo biloba, Centella asiatica and Eleutherococcus separately.